Isotope tracing study on hydrogen donating capability of supercritical water assisted by formic acid to upgrade heavy oil: Computer simulation vs. experiment. (1st August 2018) - Hosseinpour, Morteza; Fatemi, Shohreh; Ahmadi, Seyed Javad; Oshima, Yoshito; Morimoto, Masato; Akizuki, Makoto
Graphical abstract: Highlights: In-situ upgrading of heavy oil in supercritical water (SCW) in the presence of formic acid. Study on selecting the best equation of state model in ASPEN suitable for organic compound in supercritical water. Simulation with experiment study on decomposition of formic acid in supercritical water. Tracking the portion of heavy oil hydrogenation by SCW via isotope labeling technique. Abstract: Due to the increasing attention of the experts working in refineries on innovative techniques for heavy oil upgrading, the current research is focused on in-situ upgrading of heavy oil in supercritical water (SCW) assisted by formic acid. In dry condition, formic acid (FA) decomposes by two parallel paths, namely decarboxylation (HCOOH → H2  + CO2 ) and dehydration (HCOOH → CO + H2 O) to produce hydrogen and carbon mono oxide, respectively. Water-gas shift (WGS) reaction which is taken place by SCW and carbon monoxide provides active hydrogen (AH) as a more favorable hydrogen source for upgrading heavy oil in SC condition. In the current study, first, thermodynamic simulation of FA decomposition in SCW was studied to evaluate the contribution of hydrogen from water in Aspen suite environment by performing sensitivity analysis. Here, the effects of operational parameters (temperature, pressure, FA to water ratio) were studied on the above-mentioned reaction. The simulation results as well as experimental data show that the increase of FA to water ratio (FA/W) enhances the contribution of dehydration path, which means that SC works better as a precursor of hydrogen due to the higher concentrations of CO at SC condition. In order to specify the portion of hydrogen from WGS and decarboxylation reaction, the isotope labeling technique was applied by replacing ordinary water (H2 O) with heavy water (D2 O) in SC condition in the presence of heavy oil and FA. After combining the experimental data and Hansen solubility parameter of water (δH ), it was revealed that temperature has dual effects which can influence on coking reaction by physical and chemical reaction. It means that an increasing in temperature can suppress the coke formation due to better miscibility of oil with water, while at an extreme temperature condition (500 °C), the dominant condensations of polycyclic aromatics are conspicuous; consequently the rate of coking is enhanced. High pressures (∼45 MPa) also lead to the more coking reaction through the influence on the phase behavior of oil-water (δH and AH%) in which asphaltene conversion path is converted to coke rather than light products. Accordingly, T = 450 °C and Pw  = 27 MPa were proposed respectively as an appropriate temperature and pressure for heavy oil upgrading in supercritical water assisted by FA to cause less coke and produce more light liquid products.